Combination of leukocyte and platelet–rich fibrin and demineralized bovine bone graft enhanced bone formation and healing after maxillary sinus augmentation: a randomized clinical trial - de Almeida Malzoni, Carolina Mendonça [UNESP]; Pichotano, Elton Carlos [UNESP]; Freitas de Paula, Luiz Guilherme [UNESP]; de Souza, Ricardo Violante; Okamoto, Roberta [UNESP]; Austin, Rupert S.; Marcantonio Jr, Elcio [UNESP]; de Molon, Rafael Scaf [UNESP]; Zandim-Barcelos, Daniela Leal [UNESP] (Springer Nature, 2023)
Background and objectiveThe resorption of alveolar ridge bone and maxillary sinus pneumatization are challenges to implant-supported prosthetic rehabilitation. Bone regeneration using bone substitutes and growth factors are alternatives for maxillary sinus augmentation (MSA). Therefore, we sought to evaluate the effects of the association between leukocyte and platelet–rich fibrin (L-PRF) and deproteinized bovine bone mineral (DBBM) in MSA procedures.Materials and methodsThirty-six maxillary sinuses from 24 individuals were included in this randomized clinical trial. The maxillary sinuses were randomly grafted with LPRF and DBBM (test group) or grafted only with DBBM (positive control). Dental implants were installed in the test group following two periods of evaluation: after 4 (DBBM+LPRF4) and 8 (DBBM+LPFR8) months of sinus graft healing, while the control group received implants only after 8 months. Cone beam computed tomography (CBCT) was taken 1 week after surgery (T1) and before implant placement (T2). Bone samples were collected during implant placement for histomorphometric and immunohistochemical (IHC) analysis. The primary implant stability was assessed by resonance frequency analysis.ResultsCBCT analysis demonstrated a significant decrease in bone volume from T1 to T2 in all groups without differences among them. Histologically, the test group showed significantly increase in bone neoformation in both periods of evaluation (LPRF+DBBM4: 44.70±14.01%; LPRF+DBBM8: 46.56±12.25%) compared to the control group (32.34±9.49%). The control group showed the highest percentage of residual graft. IHC analysis showed increased staining intensity of osteocalcin (OCN), vascular endothelial growth factor (VEGF), and runt related transcription factor 2 (RUNX-2) in LPRF+DBBM4 group, and osteopontin (OPN) in the L-PRF+DBBM8. Primary implant stability was successfully achieved (above 60 in implant stability quotient) in all the evaluated groups.ConclusionCombination of L-PRF and DBBM increased and accelerated new bone formation allowing early implant placement probably due to the higher protein expression of RUNX2, VEGF, OCN, and OPN. These data suggest that the use of L-PRF might be an interesting alternative to use in combination with DBBM for augment the maxillary sinuses allowing the installation of appropriate length implants in shorter period of time.Clinical relevanceThis study showed improvement in bone neoformation and accelerated healing when associating L-PRF and DBBM for maxillary sinus augmentation procedures.Trial registrationThis study was registered before participant recruitment in Brazilian Registry of Clinical Trials (ReBEC - RBR-95m73t).